Outcomes after Hallux Rigidus surgery: Are we measuring what is important to patients? A qualitative analysis of patient-identified outcomes - Alison W. Henderson; Sienna L. Williams; Jay Crary; Bruce Sangeorzan; William Ledoux; Pamela Fairchild; Daniel C. Norvell (PLoS ONE, 2025)
Background Hallux rigidus (HR) is the most common form of arthritis in the foot. The joint pain and loss of motion from HR experienced during walking may lead to a significant reduction in activity and quality of life, and advanced cases may require surgery. HR surgical outcomes are often evaluated quantitatively with more generic measures not designed specifically to assess HR outcomes. The goal of these study was to determine outcomes that are important to patients with HR, possibly those that are not addressed by more general foot and ankle measures. Methods Semi-structured interviews with HR surgical patients 4–9 years after surgery were conducted. Interviews were analyzed using a team-based, iterative inductive-deductive approach to identify outcomes important to patients. Results Ten patients were interviewed; five who received motion-sparing surgery and five with fusion surgery. From interviews, seven themes were identified: pain, first MTPJ motion, walking ability, physical activity, footwear, forefoot appearance, and pain in other areas of the body. Conclusions Post-HR surgery patients indicated outcomes of importance that are not addressed by more general instruments. Specifically, forefoot appearance and pain in other areas of the body are not addressed by commonly used instruments. In addition, patient experiences of pain are more granular and HR-specific than the generic pain items used by other instruments. Patients facing HR surgery may benefit from outcome measures that are more specific to the HR surgical experience and include outcomes that patients share are important to them that are not included in commonly used outcome instruments.